The Morphological and Syntactic Use of Poetic Evidencein the Exegesis (Al-Jami’ li Ahkam al-Qur’an) by Al-Qurtubi: An Applied Study on Surah An-Nur" - Al-Mabrouk Salem, Hafsa Al-Tahir (Sharwes Scientific Journal, 2025)
This paper looks at how Al-Qurtubi used poetic evidence to explain grammatical and morphological points in his Qur’anic commentary Al-Jami’ li Ahkam al-Qur’an, focusing on examples from Surah An-Nur. The study uses a descriptive approach to gather and categorize the poetic lines based on their grammatical and morphological functions, and then applies an analytical method to understand how they contribute to the interpretation of the text. The goal is to shed light on the role poetry played in supporting Al-Qurtubi’s explanations and how he used it to clarify linguistic aspects of the Qur’an.The paper is structured into an introduction, three main sections, and a conclusion. The first section gives a brief biography of Al-Qurtubi and an overview of his tafsir. The second explains what poetic evidence is and the different types he used. The third section dives into how he applied this poetry in his commentary on Surah An-Nur—first by looking at examples tied to morphology, then those related to syntax. The conclusion sums up the key findings, most notably how Al-Qurtubi often used poetry to back up the opinions he favored in grammatical debates.